Personal Branding on Instagram: Visual Framing Analysis on The West Java Governor Candidates Online Campaign - Rizkavirwan, Darfi; Tirtadarma, Edo (Idealogy Journal; Vol 7 No 1 (2022): Idealogy Journal (April 2022), 2022)
In 2018, it was one of the most important year in Indonesia, all Indonesian people celebrate the moment of the election, in every aspect. They can choose Governor, Mayor, and Regent.  One of the area that participate in this moment, is West Java. This area is one of the most important and crucial in the election process because West Java has the highest votes compare to other area in Indonesia. West Java run the election for choosing the Governor position in 2018, and this become a unique point of interest because West Java has unique candidate, and becomes magnet to the people in that area that participate in the election event. One other consideration why this event becomes more interesting because west java has an important role in Indonesian Government, because this area has the largest population. Apart from political lobbying behaviour, and political interference, each Governor candidate that runs in this election event, should has a unique set of strategic communication in their goals to rise their awareness and electability in front of the west java’s audience. To get a better results in electability variable, they should has a good personal branding to communicate the positive value to their supporters and the audience. According to Montoya, personal branding can set or help the audience build a perspective to someone combine with a organic storytelling and the perspective was built naturally inside the mind of the audience (2002;27). One of many ways to build perception is to framing they self with the image that they want to deliver in front of the people so they can have achieved the political campaign goals. visual framing is crucial when it comes to managing key audiences’ impressions, gaining legitimacy and securing competitive positioning (Meyer et al., 2013). One of the platform to help achieve a good visual framing is through Social Media, Instagram. Instagram as one of the most popular media in Indonesia, hold major key role in moulding a good perception and perspective in  people’s mind about each candidate in  West Java Governor Election. With this framing and analysis content approach in each Instagram Visual, as the results is the themes about visual framing that want to be communicated as part of strategic communication personal branding from four candidate West Java Governor election, such as Ridwan Kamil, Sudrajat, Deddy Mizwar and Tubagus Hasanuddin. Keywords : Personal Branding; Political Branding; Visual Framing